Mitigating Psychic Distance and Enhancing Internationalization of Fintech SMEs from Emerging Markets: The Role of Board of Directors. (3rd April 2021) - Puthusserry, Pushyarag; Khan, Zaheer; Nair, Smitha R.; King, Timothy
Abstract: Prior research suggests that corporate boards and directors play important roles in firm strategy and performance. In this paper, we examine an important yet under‐explored avenue and focus on their role in overcoming the multilevel psychic distance (PD) faced by internationalizing small and medium‐sized enterprises (SMEs) originating from an emerging market. Analysing Indian Fintech SMEs, using multiple case studies, our findings reveal that boards contribute important network‐level resources and knowledge about foreign markets, which in turn assists internationalizing SMEs in mitigating PD. We demonstrate that the human and social capital of boards play important, yet distinctly different, roles in mitigating PD at pre‐ and post‐internationalization phases. At the pre‐internationalization phase, directors' prior international and industry experience, as well as board interlocks and prior connections, are most valuable, whereas at the post‐entry phase, transnational boards, and those with stronger trust‐based personal relationships (i.e. greater depth of social capital, facilitate faster experiential learning. Taken together, our findings contribute novel insights into the mechanisms through which boards affect the outcomes of firms operating, and originating from, extreme institutional environments. Further, we draw implications for research and practice.